Normative Analysis of the Weaknesses in the Regulation of Women's Representation in Legislative Elections - Syifa Salsabila Satirah; Husni Husni; Zahratul Idami (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Women's representation in legislative elections is a fundamental aspect of democracy, equality, and the protection of human rights. Indonesia has implemented affirmative action through various legal instruments, including the requirement that women occupy at least 30% of political party leadership positions and legislative candidate lists. However, these policies have not yet ensured substantive representation of women in legislative institutions, indicating persistent regulatory challenges in fulfilling women's political rights. This study aims to analyze the legal framework governing women's representation in legislative elections and identify its juridical weaknesses. The research employs a normative legal method using statutory, conceptual, and comparative approaches. Data were collected through library research on primary, secondary, and tertiary legal materials and analyzed qualitatively using the theories of legislation, legal systems, legal certainty, and legal reform. The findings show that women's representation has a strong legal basis in the 1945 Constitution of the Republic of Indonesia, Law No. 7 of 1984 on the ratification of CEDAW, and Law No. 7 of 2017 on General Elections. Nevertheless, the current framework primarily emphasizes compliance with candidate quotas without guaranteeing the election of women candidates. In addition, regulatory harmonization remains limited, while political parties have not optimally fulfilled their role in recruiting and developing female political cadres. Therefore, legal reform is necessary through improving regulatory substance, strengthening institutional mechanisms, and fostering a legal culture that supports gender equality to achieve more substantive women's representation in legislative institutions.